A Review: Prototype Gyro-Stabilizer for Buoys - Nardi; Amir Aziz Al Awwabin; Adi Widiatmoko (Journal of Computation Physics and Earth Science (JoCPES), 2021)
With buoys, tsunami waves caused by underwater earthquakes can be detected. The buoy will monitor and record changes in the sea level in the ocean. Indonesia has already installed several tsunami buoys. Nine buoys were made by Indonesia, two buoys made by America, one buoy from Malaysia, and the other nine buoys donated by Germany. These buoys are placed at all points in the Indonesian seas, such as in the Sumatra, Java, Flores, Maluku, and Banda Seas, so they can assist the Meteorology, Climatology and Geophysics Agency (BMKG) in providing tsunami early warnings. But unfortunately, the tsunami buoy network was not functioning from 2012 to 2018, because it was damaged and lost. Therefore, a tool is needed to maintain the presence, function, and performance of the buoy system so that it can operate properly. A Gyro-Stabilizer device can maintain the stability of the buoy. The Gyro-Stabilizer prototype is made of a simple circuit: a DC motor with a speed of around 18000 rpm and a mechanical gyroscope. The power supply uses the same power supply used by the buoy itself. As long as the Gyro-Stabilizer keeps rotating it will maintain the orientation of the buoy and make it stable. With good buoy stability, the durability and function of the electronic components inside can be maintained because the impact force from waves or sea waves can be reduced by using this Gyro-Stabilizer.